The Fuel System Modification To Strengthen Achievement And The Prospect Of Utilizing Gasoline Ethanol Blended With Water Injection - Wawan Purwanto; Tung-Kwan Liu; Hasan Maksum; Ahmad Arif; Muhammad Yasep Setiawan; Muhammad Nasir (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This research proposes a fuel system conversion from a carburetor to an electronic fuel injection (EFI), to save fossil fuels using gasoline-ethanol combined with water injection. Beneficial as an offer for Indonesian motorcycle environmental friendliness in terms of exhaust emissions. The goal of this study is to improve engine performance and accommodate technology for the deployment of ethanol gasoline implementations. The experiment was conducted using fuel with a ration octane number (RON) of 92, gasoline-ethanol was executed up to E25 then applied water injection (Wi). The results show that converting a conventional carburetor to EFI and additional water injection increases engine performance, mileage, and reduces exhaust emissions.